The use of herbal medicines by the elderly in rural area in Indonesia: A cross-sectional study among Acehnese - Suryawati Suryawati; Sarah Firdausa; T. Hidayat Syah; Vera Dewi Mulia; Hijra Novia Suardi; Zahratul Aini; Fauzul Husna; Hafni Andayani (Trends in Infection and Global Health, 2023)
The use of herbal medicines has become increasingly popular worldwide. Elderly has been associated with higher consumption of many medications, including herbal medicines. However, there is a lack of documentation of medicinal herbs use among Acehnese population. Our study aimed at evaluating the profile of herbals use among the elderly population in a rural area of Aceh Province, Indonesia. A cross-sectional study was conducted from October to November 2021 in Nagan Raya Regency of Aceh. To collect information on the use of herbs, a set of structured questionnaires was utilized. The data were presented in percentage (%). A total of 100 respondents were included comprising 54.0% female and most of the respondents aged between 60–64 years (43.0%). The largest percentage of the participants made their own herbal medicines (45.0%) and used them routinely as a habit (36.0%). About 75.0% of the elderly felt better and almost all of them (96.0%) reported no adverse reaction following herbs consumption. A total of 39 plant species were used by the respondents with Annona muricate L. was the most frequently used medicinal plant (16.0%) and leaves were the most commonly used parts (68.4%). Most of the herbs were prepared through boiling and squeezing (32.6%), and mainly used in the form of a drink (77.3%). Cough treatment with herbs made up 19.3%, followed by hypertension (18.0%), flatulence (7.6%), dyspepsia (5.8%), and fever (5.8%). Our investigation revealed consistency in the use of some medicinal herbs in the present study with published experimental data. However, since elderlies are often considered vulnerable individuals, the practice of herbal self-remedies among this population should be well-monitored.